A low cost one pot synthesis of biodiesel from waste frying oil (WFO) using a novel material, β-potassium dizirconate (β-K2Zr2O5). (15th June 2016) - Singh, Veena; Bux, Faizal; Sharma, Yogesh Chandra
Highlights: A novel heterogeneous catalyst β-potassium dizirconate (β-K2 Zr2 O5 ) was used for FAME production. 96.85% conversion of biodiesel from waste frying oil is achieved directly with the catalyst. The catalyst is stable up to five cycles without substantial loss in activity. Abstract: Biodiesel was synthesized from waste frying oil (WFO) using β-potassium dizirconate (β-K2 Zr2 O5 ) as a novel heterogeneous catalyst. Synthesized catalyst was characterized by X-ray diffractometry (XRD), thermogravimetric analysis (TGA), attenuated total reflectance fourier transform infrared spectroscopy (ATR-FTIR), particle size analyser, scanning electron microscopy (SEM), BET surface area and basicity. Various reaction conditions such as molar ratio of methanol: oil, catalyst amount (wt%), reaction temperature, time and reusability of catalyst were studied for transesterification reaction with the catalyst, β-K2 Zr2 O5 . High biodiesel conversion of 96.85% was observed at a 10:1 M ratio (alcohol: oil), 4 wt% catalyst at 65 °C for 2 h. WFO was characterized by GCMS and biodiesel conversion was ascertained by Fourier transform nuclear magnetic resonance ( 1 H and 13 C FTNMR) spectroscopy. It was first time that β-potassium dizirconate was used as a catalyst for biodiesel synthesis. The catalyst was reused up to five times without significant loss in its activity. Physical and chemical properties of FAME such as flash point, fire point, cloud point, density, and kinematic viscosity were deliberated.